Opozycyjna myśl polityczna wobec narastającego kryzysu społeczno-gospodarczego i PRL w drugiej połowie lat siedemdziesiątych - Brzechczyn, Krzysztof (Instytut Pamięci Narodowej - Komisja Ścigania Zbrodni przeciwko Narodowi Polskiemu, 2020)
The purpose of the article is the analysis of ways of presenting the social & economic crisis using selected examples of oppositional political thought. The author provides examples of the phenomenon of infiltration between the official and unofficial areas, and then analyses the pro gram Notes about the economic situation of the country and the main threads in the discussion about it in the national independent magazine ‘Głos’ (Voice) and in the emigration magazine ‘Aneks’ (Annex). In the further part, he presents the issue of the explosion of social discontent in political thought by Jacek Kuroń and Leszek Moczulski. Based on similar sets of premises, each in a different way formulated achievable goals for political actions. Kuroń offered a com promise to the PZPR (Polish United Workers’ Party), while Moczulski foreshadowed depriving the communists of their power. The article compares three interlocking issues occurring in the social & political reflection of both activists: the organizational form of the opposition, operat ing strategy with respect to deepening social & economic and political crisis, as well as their attitude towards the threat of Soviet intervention
Keywords: kryzys; PRL; historia PRL; opozycja polityczna; drugi obieg; KSS KOR